2017
DOI: 10.1111/1365-2664.12858
|View full text |Cite
|
Sign up to set email alerts
|

Grape moth density in Bordeaux vineyards depends on local habitat management despite effects of landscape heterogeneity on their biological control

Abstract: 1. Biological control of crop pests is a major ecosystem service affected by several variables acting at multiple spatial scales. Among these variables, heterogeneity at the habitat and landscape scales are known key drivers of trophic interactions and pest density in agroecosystems. However, studies that try to disentangle their relative effects in perennial cropping systems are scarce and nothing is known about their impacts on insect pest density and pesticide applications. 2. We examined the effect of hete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 45 publications
5
42
1
Order By: Relevance
“…This confirmed that several biological control functions can have opposite responses to management intensity (Rusch et al. ). Direct negative effects of pesticides on natural enemies may limit the biological control potential of grape moths, which explains the negative relationships between crop productivity or pesticide use and biological control services (Geiger et al.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…This confirmed that several biological control functions can have opposite responses to management intensity (Rusch et al. ). Direct negative effects of pesticides on natural enemies may limit the biological control potential of grape moths, which explains the negative relationships between crop productivity or pesticide use and biological control services (Geiger et al.…”
Section: Discussionsupporting
confidence: 71%
“…Our analyses particularly revealed that increasing pesticide use decreased the removal rates of moth eggs and increasing crop productivity decreased the removal rates of moth eggs while increased weed seed removal. This confirmed that several biological control functions can have opposite responses to management intensity (Rusch et al 2017b). Direct negative effects of pesticides on natural enemies may limit the biological control potential of grape moths, which explains the negative relationships between crop productivity or pesticide use and biological control services (Geiger et al 2010, Bommarco et al 2011).…”
Section: Effects Of Specific Farming Practices On Biological Controlsupporting
confidence: 54%
See 1 more Smart Citation
“…This is similar to the case of Spain with the Integrate Pest Management (IPM), or the case of France that has tried to adopt agroecological innovations aimed at reducing the use of pesticides for banana production in the French Antilles [49]. In this regard, Rusch et al [50] reported the positive and practical effects of the ecological intensification through the heterogeneity of the landscape in the biological control of vineyard pests, maintaining that the monitoring of these practices by farmers is an original approach that seeks to identify and analyze alternative systems and supports the development of these techniques. According to Phocas et al [51], agroecology uses ecological processes and local resources instead of chemical inputs to develop productive and resilient systems.…”
Section: Agroecology As Agricultural Practice In Crop Productionmentioning
confidence: 80%
“…Other authors have used plasticine models (commonly used to compare attack rates across gradients) to comparatively approach levels of avian insectivory on pests (reviewed in Bateman, Fleming, & Wolfe, 2017). This method have proven useful to explore the effects of agricultural management and landscape heterogeneity on overall pest control (Rusch, Delbac, Thiéry, & Thi Ery, 2017), avian pest control in vineyards (Barbaro et al, 2017) or even to find global latitudinal/altitudinal patterns on predation rates (Roslin et al, 2017). Also, the abundance of insectivorous birds and their predation on plasticine caterpillars has positively been linked to structural heterogeneity (Bereczki, Ódor, Csóka, Mag, & Báldi, 2014).…”
Section: Introductionmentioning
confidence: 99%